The Military Coup of September 12, 1980, in Turkey and Political Developments - Petrosyan, Hayk (History and Culture, 2026)
On September 12, 1980, the military coup that took place showed the unstable situation inside the country. It should also be noted that the elite of the Turkish army, before starting the military coup, had intensive meetings with high-ranking US statesmen for a long time. In the end, after all this was successfully accomplished, the perpetrators of the military coup became the government in the country. Thereby, the "Kurdish movement" was also eliminated, which was also discussed by the military elite. Political parties were not banned, but their public activities were banned; the actual political life was in the hands of the military elite.
Keywords: Turkey; military coup; armed forces; Kenan Evren; NSC; Constituent Assembly